1984
DOI: 10.1002/chin.198409113
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: FLUORIDE‐INDUCED 1,2‐ELIMINATION OF O‐(TRIMETHYLSILYL)PHENYL TRIFLATE TO BENZYNE UNDER MILD CONDITIONS

Abstract: Das aus dem Silylether (I) zugängliche Triflat (II) wird durch die Fluoride (III) in Dehydrobenzol (IV) übergeführt, das mit Furan (V) zum Addukt (VI) und mit den Alkoholen (VII) zu den Phenolethern (VIII) weiterreagiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…1 Several methods have been used for aryne generation (Scheme 1). 2 Pathway A involves lithium-halogen exchange followed by LiX elimina tion. This methodology is limited by alkyllithium reactivity that precludes use of many common functionalities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Several methods have been used for aryne generation (Scheme 1). 2 Pathway A involves lithium-halogen exchange followed by LiX elimina tion. This methodology is limited by alkyllithium reactivity that precludes use of many common functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Early investigations involved use of hydroxide, alkoxide, or amide (NaNH 2 ) bases which trapped the formed arynes. 2c,d Deprotonation of aryl fluorides with a BuLi/NaOtBu mixture or aryl chlorides with BuLi allowed reactions to proceed at low temperatures; however, this method for aryne generation is incompatible with many functional groups due to high reactivity of alkyllithium reagents. 2f,g Lithium amide bases such as LDA or lithium tetramethylpiperidide could be used at low temperatures as well.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terms & Conditions of access and use can be found at http://www.tandfonline.com/page/terms-and-conditions Arynes as useful reactive intermediates have received considerable attention in synthetic applications. [1] Before Himeshima et al first reported that 2-(trimethylsilyl)phenyl triflate 1 can generate arynes under mild conditions, [2] the general method for its generation was deprotonation from aromatic halogen compounds with a strong base, which is unfavorable to some substrates containing base-sensitive functional groups. Recently, using 1 as a precursor, reactions (especially a variety of nucleophile addition to arynes) have been studied for synthesizing polysubstituted arenes, which otherwise are difficult to prepare.…”
mentioning
confidence: 99%